2020
DOI: 10.3389/fneur.2020.540156
|View full text |Cite
|
Sign up to set email alerts
|

AQP4-IgG and MOG-IgG Related Optic Neuritis—Prevalence, Optical Coherence Tomography Findings, and Visual Outcomes: A Systematic Review and Meta-Analysis

Abstract: Background: Optic neuritis (ON) is a cardinal manifestation of multiple sclerosis (MS), aquaporin-4 (AQP4)-IgG-, and myelin oligodendrocyte glycoprotein (MOG)-IgG-associated disease. However, the prevalence of AQP4-IgG seropositivity and MOG-IgG seropositivity in isolated ON is unclear, and studies comparing visual outcomes and optical coherence tomography (OCT)-derived structural retinal measures between MS-ON, AQP4-ON, and MOG-ON eyes are limited by small sample sizes. Objectives: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
52
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 115 publications
6
52
1
Order By: Relevance
“…In a study of conventional-dose RTX for NMOSD, the reduction rate of ARR ranged from 25% to 100% ( 6 8 , 10 , 20 ). We considered that the studies with relatively low effectiveness of RTX have the following commonalities: (1) patients included in most of the studies were diagnosed with NMO or long segment myelitis, which had higher EDSS scores than our ON patients; (2) positive serum AQP4-Ab was not included in the inclusion criteria in many studies, and patients with negative AQP4-Ab may have different pathological mechanisms, such as myelin oligodendrocyte glycoprotein antibody or glial fibrillary acidic protein antibody mediated autoimmunity ( 21 23 ); and (3) in some studies, RTX was used in refractory NMO treatment. Patients uncontrolled by other immunosuppression therapies might have higher disease activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of conventional-dose RTX for NMOSD, the reduction rate of ARR ranged from 25% to 100% ( 6 8 , 10 , 20 ). We considered that the studies with relatively low effectiveness of RTX have the following commonalities: (1) patients included in most of the studies were diagnosed with NMO or long segment myelitis, which had higher EDSS scores than our ON patients; (2) positive serum AQP4-Ab was not included in the inclusion criteria in many studies, and patients with negative AQP4-Ab may have different pathological mechanisms, such as myelin oligodendrocyte glycoprotein antibody or glial fibrillary acidic protein antibody mediated autoimmunity ( 21 23 ); and (3) in some studies, RTX was used in refractory NMO treatment. Patients uncontrolled by other immunosuppression therapies might have higher disease activity.…”
Section: Discussionmentioning
confidence: 99%
“…Although OCT has been used for the evaluation of ON in NMO or MS in many studies, longitudinal observation studies have been rare. It is reported that NMO-ON eyes have lower peri-papillary retinal nerve fiber layer and macular ganglion cell + inner plexiform layer thicknesses, as well as a “flater” disc when compared with MS-ON eyes ( 21 , 37 ). Moreover, while MS-ON mostly affected the small-diameter neurons in the temporal quadrant of the optic disc, NMO-ON more affected the nerve fibers above and below the optic disc ( 38 , 39 ), consistent with the results in this study.…”
Section: Discussionmentioning
confidence: 99%
“…This result was consistent with a recent meta‐analysis study. (Filippatou et al., 2020) Patients with NMOSD had significantly smaller whole VD and PD areas than those with MS. A recent study showed that NMOSD + ON eyes were associated with worse visual outcomes than MS + ON eyes, even with similar severity of their macular GC‐IPL thinning. (Sotirchos et al., 2020) Our results confirm this finding.…”
Section: Discussionmentioning
confidence: 95%
“…The most common retinal abnormality during OCT assessments of the MS and NMOSD groups is a thinning of the peripapillary retinal nerve fiber layer (pRNFL) and the macular ganglion cell‐inner plexiform layer (GC‐IPL). (Bennett et al., 2015; Fernandes et al., 2013; Filippatou et al., 2020; Lange et al., 2013; Merle et al., 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta‐analysis of the prevalence of AQP4‐IgG and MOG‐IgG ON reports a prevalence of AQP4‐IgG of 27% in the Asian population and 4% in non‐Asian adult patients with isolated ON, whereas MOG‐IgG seroprevalence was 20% in Asians and 8% in non‐Asians 55 …”
Section: The Course Of Optic Neuritis (Isolated Recurrent Chronic Amentioning
confidence: 99%